101k views
5 votes
-10x + 3(8 + 8x) = -6(x - 4) solve for x

User Siva Cn
by
5.4k points

2 Answers

5 votes

Answer:

x = 0

Explanation:

Solve for x:

3 (8 x + 8) - 10 x = -6 (x - 4)

3 (8 x + 8) = 24 x + 24:

24 x + 24 - 10 x = -6 (x - 4)

Grouping like terms, 24 x - 10 x + 24 = (-10 x + 24 x) + 24:

(-10 x + 24 x) + 24 = -6 (x - 4)

24 x - 10 x = 14 x:

14 x + 24 = -6 (x - 4)

Expand out terms of the right hand side:

14 x + 24 = 24 - 6 x

Add 6 x to both sides:

14 x + 6 x + 24 = (6 x - 6 x) + 24

6 x - 6 x = 0:

14 x + 6 x + 24 = 24

14 x + 6 x = 20 x:

20 x + 24 = 24

Subtract 24 from both sides:

20 x + (24 - 24) = 24 - 24

24 - 24 = 0:

20 x = 24 - 24

24 - 24 = 0:

20 x = 0

Divide both sides of 20 x = 0 by 20:

(20 x)/20 = 0/20

20/20 = 1:

x = 0/20

0/20 = 0:

Answer: x = 0

User Najathi
by
5.4k points
5 votes

Answer:x=0

Explanation:

User Alex Nguyen
by
5.4k points